Designing an English Course Materials with Islamic Values in Islamic Institution - Hasibuan, Kalayo; Khairun Nisa; Steviona Eliza (Journal of Applied Linguistics, 2025)
Language and culture are inseparable, as language reflects cultural values. The spread of English throughout the world has brought Western cultural influences that can conflict with Islamic values, especially in Indonesia. This research investigates the development of English learning materials that integrate Islamic values, focusing on English for Specific Purposes (ESP) in Islamic educational institutions. This research utilizes a qualitative approach by using document analysis to identify effective learning strategies. The results show that the integration of Islamic values can be achieved through various techniques, such as code-switching, contextual connections with Islamic teachings, and culturally relevant examples in literature teaching. The results highlight the importance of adapting educational content to Islamic values while improving language proficiency. The findings have important implications for the development of culturally appropriate learning materials in Islamic educational institutions Keywords : English material. Islamic values. English for specific purposes. Cultural integration